Alterman, Jon B. y John W. Garver, The Vital Triangle: China, The United States and The Middle East, Washington, D.C., The CSIS Press, 2008. - Elías Miranda, Víctor M. (Estudios de Asia y África, 2009)
Alterman, Jon B. y John W. Garver, The Vital Triangle: China, The United States and The Middle East, Washington, D.C., The CSIS Press, 2008.